Commentary on thrombotic and bleeding complications of clinical trials of growth factor inhibitors (Hematology Meeting Reports, 2009)
A number of naturally occurring and pathologic growth factors have been identified in recent years to play pivotal roles in the growth and metastastic potential of various cancers. As such, they have emerged as interesting targets for the development of novel therapeutic inhibitory agents and intervention strategies in the cancer patient. Extensive preclinical and clinical trial results with growth factor inhibitors have indicated that there is close interplay between hemostasis, humoral anticoagulation, and fibrinolytic mechanisms and the interference of these integral growth factors in cancer cells.1 These interactions may provide explanations for some of the thrombotic and hemorrhagic complications associated with their administration.